Management of Corporate Training and Decision-Making about Training - Ya. Yu. Pavlov; I. K. Evseeva; I. L. Kazakova (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The article studies corporate training in general as a line in research and a concrete issue about the degree of investigation of the issue of decision-making in this sphere of activity. The issue of decision-making is fundamental for management of corporate training, as training model depends on this mechanism. In previous studies this issue was touched upon only indirectly. To study this problem deeply it is necessary to understand the topical level of research on mentioned-above direction. The goal of the article is to study methods used in this sphere and current condition of this field of academic research. In order to attain the goals of the research descriptive literature review of sources from the international database Web of Science was carried out focusing on studying methodology and level of theoretical investigation. As a result the article identified several key trends in studying corporate training and revealed predominance of quantitative works even in conditions of insufficient theoretical investigation. Works being analyzed more often used concepts of training organization by K. Watkins and V. Marsic and the model of digital maturity by A. Back and S. Berhause.